The benefit of paracentesis on hospitalized adults with cirrhosis and ascites. Issue 5 (May 2016) - Gaetano, John N; Micic, Dejan; Aronsohn, Andrew; Reddy, Gautham; Te, Helen; Reau, Nancy S; Jensen, Donald
Abstract: Background and Aim: The aim of this study is to assess paracentesis utilization and outcomes in hospitalized adults with cirrhosis and ascites. Methods: The 2011 Nationwide Inpatient Sample was used to identify adults, non‐electively admitted with diagnoses of cirrhosis and ascites. The primary endpoint was in‐hospital mortality. Variables included patient and hospital demographics, early (Day 0 or 1) or late (Day 2 or later) paracentesis, hepatic decompensation, and spontaneous bacterial peritonitis. Results: Out of 8 023 590 admissions, 31 614 met inclusion criteria. Among these hospitalizations, approximately 51% (16 133) underwent paracentesis. The overall in‐hospital mortality rate was 7.6%. There was a significantly increased mortality among patients who did not undergo paracentesis (8.9% vs 6.3%, P  < 0.001). Patients who did not receive paracentesis died 1.83 times more often in the hospital than those patients who did receive paracentesis (95% confidence interval 1.66–2.02). Patients undergoing early paracentesis showed a trend towards reduction in mortality (5.5% vs 7.5%) compared with those undergoing late paracentesis. Patients admitted on a weekend demonstrated less frequent use of early paracentesis (50% weekend vs 62% weekday) and demonstrated increased mortality (adjusted odds ratio 1.12 95% confidence interval 1.01–1.25). Among patients diagnosed with spontaneous bacterial peritonitis, early paracentesis was associated with shorter length of stay (7.55 vs 11.45 days, P  < 0.001) and decreased hospitalization cost ($61 624 vs $107 484, P  < 0.001). Conclusion: Paracentesis is under‐utilized among cirrhotic patients presenting with ascites and is associated with decreased in‐hospital mortality. These data support the use of paracentesis as a key inpatient quality measure among hospitalized adults with cirrhosis. Future studies are needed to investigate the barriers to paracentesis use on admission.